The Transport-Building Cycle in Urban Development: Chicago - Isard, Walter; Isard, Caroline (The Review of Economics and Statistics, 1943)
AN article in an earlier issue of this REVIEW 1 demonstrated the presence of the transport-building cycle in several important and comprehensive economic series for the United States. Mention was made of the relation of this cycle to another basic aspect of United States development, namely, urban growth. In the present note, specific consideration will be given to the existence of the transport-building cycle in the physical growth of the city of Chicago.2 Chart i is composed of a reference transportbuilding pattern for the United States,3 and of series depicting the five following types of activity representative of Chicago's physical growth: land subdividing, building, lumber receipts, manufacturing (number employed), and population growth.4 Land subdividing (representing area expansion of the city), building activity (representing structural growth), and annual population increase are three series basic to any study of urban physical development. Lumber trade throughout the nineteenth century was a dominant commercial enterprise at Chicago; and the number employed in manufacturing is a rough physical measure of the city's industrial growth.5 Examination of the movements of the five series discloses cycles that correspond to those designated as transport-building cycles in the series for the United States (top curve of Chart I). The troughs occur in I838-43, I858-62, I8748o, I896-I90I, I9I7-I9, and 1930-32. For each series and for the five series as a whole, measuring from trough to trough, the length of the cycles averages around eighteen years. With respect to timing, the series are highly synchronous; moreover, comparison of the trough periods for the Chicago series with those for the United States series reveals only minor differences. Save for population growth, which shows some tendency to lead during the nineteenth century, the Chicago series conform 1 Walter Isard, A Neglected Cycle: The TransportBuilding Cycle, this REVIEW, XXIV (I942), Pp. I49-58. 2Chicago was selected for study because (i) an abundance of data, dating from the city's infancy, was available, (2) Chicago is a primary center, (3) forces causing Chicago's growth were general and affected the development of most cities. 'This reference pattern was constructed on the basis of the series presented in the aforementioned article. The heavy solid lines represent the intervals containing the troughs of the individual series for the United States. (See Walter Isard, op. cit., p. I55, Table I.) Similarly, the horizontal dashed lines represent intervals within which the peaks of these series were reached (except that of wholesale prices during the Civil War). The peak and trough intervals are connected by dashed lines. For reasons presented in the earlier article, dating of cycles is from trough to trough, and only slight significance for purposes of timing should be attached to the peak lines of the reference pattern. Moreover, this pattern should not be construed as a composite picture of United States economic growth, nor as a cycle curve. Rather, it is a rough portrayal of transportbuilding movements isolated from other fluctuations, in which no attempt has been made to ascribe turning points and various phases to the cycle. 'Data on land subdividing, building, and population are available in H. Hoyt, One Hundred Years of Land Values in Chicago (Chicago, I933), pp. 474-83. Mr. Hoyt has described cycles in Chicago real estate which correspond closely to five of the transport-building movements. He does not include, as a cycle, movements between I899 and I9I7. Apropos of building activity, both value of buildings recorded in permits and number of building permits have been charted. The movements of these two series are in close harmony; and, for the earlier years when data on number of building permits are not available, value of new buildings, though not a measure of physical growth, may be taken as indicative of such. Lumber receipts for I833-42 are estimates from Industrial Chicago (Chicago, I89I-96), Vol. III, p. I93; data for I843-7I were taken from Chicago Herald, Illustrated History of Chicago (Chicago, I887), p. 83; from I872 on, Chicago Board of Trade, Annual Report. Data on number employed in manufacturing were pieced together from numerous sources: i850, i86o: United States Census Office, 7th Census, I850 and 8th Census, i86o; I854-56, I869-70: Chicago Herald, op. cit.; I857: Daily Democratic Press, Chicago, estimates for manufacturing activity approximately the same as for I856; i86i: Chicago Board of Trade, Annual Report, I86I; I872: E. Chamberlin, Chicago and its Suburbs (Chicago, I874), p. I29; I87398, Chicago Tribune, Annual Review Section. These data are not strictly comparable and must be interpreted with caution, especially with regard to short-run movements; in describing long-run cyclical movements, it does seem permissible to use them. Annual figures for number employed in manufacturing were not obtainable after I898. To bring into stronger relief the depression of this series in the midnineties, a dashed line has been projected for several years after I898, which roughly conforms to the manufacturing growth of Chicago during those years. 'It would have been desirable to use physical output rather than number employed, but output data were not available, and it was thought highly inadvisable to deflate value statistics by a price index constructed from very scanty material.